Study of backward terahertz radiation from intense picosecond laser–solid interactions using a multichannel calorimeter system. (2019) - Liu, H.; Liao, G.-Q.; Zhang, Y.-H.; Zhu, B.-J.; Zhang, Z.; Li, Y.-T.; Scott, G. G.; Rusby, D.; Armstrong, C.; Zemaityte, E.; Bradford, P.; Woolsey, N.; et al.
Abstract : A multichannel calorimeter system is designed and constructed which is capable of delivering single-shot and broad-band spectral measurement of terahertz (THz) radiation generated in intense laser–plasma interactions. The generation mechanism of backward THz radiation (BTR) is studied by using the multichannel calorimeter system in an intense picosecond laser–solid interaction experiment. The dependence of the BTR energy and spectrum on laser energy, target thickness and pre-plasma scale length is obtained. These results indicate that coherent transition radiation is responsible for the low-frequency component ( < 1 THz) of BTR. It is also observed that a large-scale pre-plasma primarily enhances the high-frequency component ( > 3 THz) of BTR.